Study on the seroprevalance rate of leptospirosis in tertiary care hospital, Kolkata (Panacea Journal of Medical Sciences, 2025)
Background: Leptospirosis is a worldwide prevalent septicemic zoonotic disease caused by spirochaetes Leptospira having wide spectrum of illness. Animals particularly rats are the main reservoir of disease and is mainly transmitted with contaminated rain water infected with rat urine. The organisms enter our body through cuts & abrasions. The disease presents with diverse clinical presentations making confusion with other febrile illnesses.Aims & Objectives: The present study was undertaken to determine sero-prevalence & seasonal trends of Leptospirosis in surrounding locality of our hospital.Materials and Methods: This is a prospective cross-sectional study conducted at the Department of Microbiology for 1 year from January to December 2023. The inclusion criteria is patients with febrile illness more than 5 days. A total of 571 blood samples were received for Leptospira serology. Centrifuged serum sample were tested by Pan bio-ELISA KIT for qualitative detection of IgM antibody to Leptospira.Results: Amongst 571 received sample, 75 samples (13.13%) were serologically reactive by ELISA. Most of the positive cases clinically presented with fever and headache and were admitted in medicine ward. Highest seroprevalence was found more in male patients (53.3%) and in 21 to 40 years of age groups (29.3%). Period from July to September month noted to have highest prevalence.Conclusions: This study gives an idea of seropositivity rate about Leptospira in the surrounding locality of our hospital in Central Kolkata. Improvement of hygiene and sanitation can prevent transmission. Increased awareness and early diagnosis and treatment can reduce the treatment cost, morbidity and mortality.